Insegnare chimica con passione tra i banchi di scuola - De Togni, Alessandra; Giuffreda, Lucia; Orian, Laura (Chimica nella Scuola, 2024)
Insegnare chimica con passione! is the title of a volume published this year in the Epistemology and Didactics of Chemistry Series of Padua University Press, which collects contributions from numerous secondary school chemistry teachers in the Veneto region. The project, which came about as part of the Chemistry PLS, was a new experience for teachers who had the opportunity to disseminate some of the teaching and laboratory activities developed and implemented in the classroom through such an effective and interesting tool as the book. Organizing the content, collaborating with colleagues in writing the text and creating original images, actively participating in the editorial process, was a complex exercise through which the teacher-authors matured scientifically and personally, and saw their daily teaching efforts materialized in a product that is now available to many other teachers. It is precisely the effort to share experiences and exchange best practices that is a key aspect of teacher education whose work is valued and disseminated outside their classrooms. Giovanni Villani (ICCOM-CNR, Pisa) wrote the first chapter contributing as well as editor of the work together with Laura Orian and Marina Gobbo (University of Padua) to a deep reflection on the role of chemistry in our modern world. Eric Scerri (UCLA, California) edited the concluding chapter of the work after meeting and discussing with teachers the foundation and role of chemistry as a science and discipline. The presentation of the book and its contents are followed by elements of reflection on the significance of teaching chemistry in today’s schools from the perspective of secondary school teachers.